Adherence to in‐person vs. virtual delivery of a multi‐domain behavioral intervention to prevent cognitive decline: The US POINTER Study. (20th December 2022) - Katula, Jeffrey A.; Ventrelle, Jennifer; King, Katelyn; Garcia, Katelyn R; Graef, Sarah; Lovato, Laura; Wilmoth, Sharon; Woolard, Nancy; Espeland, Mark A.; Snyder, Heather M.; Kivipelto, Miia; Carrillo, Maria C.; et al.
Abstract: Background: In response to the global pandemic, U.S. POINTER procedures were adapted to include virtual intervention delivery. Here we describe the impact of this adaptation on adherence in a large community‐based lifestyle intervention trial. Method: U.S. POINTER is conducted through a partnership between the Alzheimer's Association (AA) and five clinical sites. A total of 2000 older adults at risk for cognitive decline are assigned to one of two 24‐month multi‐domain lifestyle interventions. The Self‐Guided (SG) group works toward lifestyle goals that best meet their individual needs and schedules. The Structured (STR) group follows a coordinated program with specific goals for physical activity, diet, cognitive/social challenge, and health monitoring. Both groups meet in teams of 12‐15 participants throughout the study for support and guidance, which are led by trained staff. SG teams meet six times over 24 months, and STR teams meet weekly for the first 4 months, then 2x/month for 2 months, and then monthly. Although Team Meetings for both intervention groups were planned as in‐person events, the global pandemic necessitated a pivot to virtual delivery. Result: From January through December 2021, N = 2103 Team Meetings were conducted in‐person and N = 4663 Team Meetings were conducted virtually for 824 participants. For both intervention groups, in‐person and virtual Team Meeting attendance was the same, at 90%. When Team Meetings were held in‐person, STR participants completed a median of 93 very active Fitbit minutes/week (IQR = 38, 185) and reported a median MIND Diet score of 11.0 (IQR = 9.5, 12.0). When Team Meetings were virtual, adherence metrics were comparable with median values of 101 very active Fitbit minutes/week (IQR = 43, 192) and a MIND Diet score of 11.0 (IQR = 9.8, 12.0). Blood pressure monitoring and cognitive training metrics were also comparable without regard to Team Meeting delivery format. Conclusion: Our findings demonstrate that a shift to virtual participant contact during the pandemic did not compromise adherence to a complex multi‐domain lifestyle intervention in older adults. These findings have high relevance for other ongoing lifestyle intervention studies within and outside of WW‐FINGERS, and highlight the importance of adaptability in clinical trial design and implementation to foster sustainability under challenging life circumstances.